Rheological and thermal properties of suspensions of microcapsules containing phase change materials - Cao, Vinh Duy (Colloid Polym Sci, 2018)
The thermal and rheological properties of suspensions of microencapsulated phase change materials (MPCM) in glycerol were investigated. When the microcapsule concentration is raised, the heat storage capacity of the suspensions becomes higher and a slight decline in the thermal conductivity of the suspensions is observed. The temperature-dependent shear-thinning behaviour of the suspensions was found to be strongly affected by non-encapsulated phase change materials (PCM). Accordingly, the rheological properties of the MPCM suspensions could be described by the Cross model below the PCM melting point while a power law model best described the data above the PCM melting point. The MPCM suspensions are interesting for energy storage and heat transfer applications. However, the non-encapsulated PCM contributes to the agglomeration of the microcapsules, which can lead to higher pumping consumption and clogging of piping systems.